Evaluation of Spatial Planning Policies: an appliedcomparative analysis between Portugal and Brazil - da Costa, Eduarda Marques; Antonello, Ideni Terezinha (Sociedade & Natureza, 2018)
The main objective of this article is related to the need of thinking about the evaluation and monitoring of public policies, including development policies and planning, considering that these are keytools for territorial cohesion. This analysis has two interconnected objects of study: the first is to present the methodological approach for evaluating public policy developed by the European Commission to assess the regional and sectoral policy instruments implemented in the various European regions; the second object, is its application focusing on the operational programs in Portugal and an application in Brazil.In order to approximate this methodological base with the experience of the public policies of spatial planning in the Brazilian,the law will be analyzed federal law called the City Statute (n. º10.257, 2001) and its consistency with local politics. As an example, the Master Plan of Londrina (PDPML, 2008) wasselected with the purpose of evaluating the degree of coherence between the federal urban public policy and a municipal policy.